The effect of economic policy uncertainty and herding on leverage: An examination of the BRICS countries - Prudence Makololo; Yudhvir Seetharam (Cogent Economics & Finance, 2020)
This study examines the role of economic policy uncertainty (EPU) in influencing firm performance and leverage as a form of financing decisions, in the presence of herding in the emerging markets of Brazil, Russia, India, China and South Africa (BRICS). This study contributes to our understanding of how businesses in emerging markets make financial decisions during uncertain times as well as the role of policy development in influencing firm performance and corporate decisions. The increase or decrease in EPU is determined by the way policymakers or investors act and the consequences of their decisions. EPU is, in fact, a market characteristic that brings changes in prices and returns. Therefore, investors and policymakers should be aware of it to prevent any negative effects. A steady and predictable economic policy is critical to economic growth. We investigate how firms rationalise making leverage financing decisions during times of economic policy uncertainty and if so, if herding is present in these decisions. Our data spans the Top 80 listed firms in each respective country from the beginning of June 2002 to the end of June 2017. Russian, Indian and South African results show that EPU is significant in determining leverage financing decisions and that an increase in EPU leads to herding in such decisions. We find contrary results in Brazilian and Chinese firms. Our results imply that when leverage decisions are made, both the political climate as well as competitor movement data must be considered in determining a firm's "ideal" capital structure.
Keywords: 330; BRICS; capital structure; decision making; herding; policy uncertainty